Phytochemical Marker-based Analysis, Antioxidant Potential, and Shelf-Life Study of Geographically Different Samples of Tinospora cordifolia (Stem) - Gandhi, Yashika; Mishra, Sujeet K; Kumar, Vijay; Rawat, Hemant; Kumar, Ravi; Singh, Gagandeep; Singh, Ravindra; Singh, Arjun; Narasimhaji, Ch Venkata; Srikanth, Narayanam; Acharya, Rabinarayan (Current Indian Science, 2024)
BackgroundTinospora cordifolia (TC), commonly referred to as Guduchi, holds a prominent position in the Indian traditional system of medicine and has been cited in Ayurvedic literature for its efficacy in the treatment of a range of ailments, including jaundice, urinary issues, diabetes, prolonged diarrhea, skin conditions, stomachaches, and dysentery.MethodsThe present study analyzed the content of phytochemical markers present in the stems of TC collected from five distinct geographical locations (TC-01 to TC-05) and assessed the corresponding variations in their in-vitro antioxidant potential.ResultsLupeol content in various samples of TC varied from 217.9 to 510.9 µg/mg, while palmatine ranged from 0.002% to 0.025%. Total phenolic content (TPC) ranged from 0.77 to 6.35 mg GAE/g wt., and total flavonoid content (TFC) from 12.15 to 20.03 mg QCE/g wt., with IC50 values between 21.02 and 81.81 mg/mL. Elemental analysis of TC-01 to TC-05 showed significant essential elements and permissible levels of heavy metals. A shelf-life study of TC samples indicated stability beyond three years.ConclusionThe considerable diversity in phytochemical content and antioxidant values underscores the substantial influence of geographical variation on the therapeutic potential of TC.
Keywords: Palmatine